Procedimientos de Eutanasia Humanitaria de Ganado Enfermo, Herido y/o Debilitado, Cartilla de Referencia Eutanasia en Ganado Bovino - Jan K. Shearer; Paul Nicoletti; Pedro Melendez (EDIS, 2007)
VM-159, a full-color wallet card by Jan K. Shearer, Paul Nicoletti and Pedro Melendez, is the Spanish language version of VM-155, "Quick Reference Wallet Card on Euthanasia of Cattle." It describes the correct way to humanely euthanize cattle using gunshot or penetrating captive bolt. Published by the UF Department of Veterinary Medicine -- Large Animal Clinical Sciences, April 2007.